To Excavate or not? Case of Discovery of an Early Christian Baptistery and Church at Ulpiana, Kosovo - Çetinkaya, Halûk (Actual Problems of Theory and History of Art, 2016)
Excavating a site is one of the best methods to obtain information. Our excavation in the ancient city of Ulpiana (Kosovo) is the first and so far the only Turkish excavation in Europe. During this excavation, an Early Christian baptistery and a church with floor mosaics were discovered. Although the discovery of such buildings contributed to studying regional history, there is a concern about the preservation and protection of these monuments. Hence the question arises, by excavating did we do any good or not?
Keywords: Early Christianity; baptistery; church; mosaics; Kosovo; Moesia Superior